Characteristics and patterns of residential energy consumption for space cooling in China: Evidence from appliance-level data. (15th February 2023) - Zhu, Mengshu; Huang, Ying; Wang, Si-Nuo; Zheng, Xinye; Wei, Chu
Abstract: The adoption of air conditioners (ACs) in households is rapidly growing in response to rising global temperatures, thereby posing significant sustainability challenges. It is vital to identify the characteristics and patterns of household demand for AC-induced electricity consumption. However, owing to huge costs and privacy concerns, appliance-level data sets are rare. Therefore, we conducted the Chinese Residential Energy Consumption Survey (CRECS) 2021, collected high-frequency operation data from 1140 active ACs from 673 households in 40 southern Chinese cities, and depicted the overall residential space-cooling electricity consumption profile. We found that, first, urban households in southern China showed a highly consistent pattern in AC time use. The peak usage in both living rooms and bedrooms occurred at noon (11 a.m.–3 p.m.) and night (9 p.m.–1 a.m.), when electricity consumption was 29%–38% higher than at other times of the day. Second, AC usage patterns showed great heterogeneity in terms of city-level and household-level characteristics. Households in large cities typically owned less energy-efficient equipment and consumed more AC-related electricity than did those in mega- and small-and-medium cities. Middle-income households, smaller room sizes, less-educated heads of households, and households with older adults were associated with lower AC-related electricity use. Highlights: Residential air conditioning electricity consumption profile was created. Data from 1140 active ACs from 673 households in southern China were examined. AC usage patterns and use of energy-efficient equipment differed by city size. Middle-income households and smaller room sizes used less electricity. Households with less-educated heads and with older adults used less electricity.